The 330 risk loci known for systemic lupus erythematosus (SLE): a review - Laurynenka, Viktoryia; Harley, John B. (Frontiers in Lupus, 2024)
A careful review of literature to 2023 shows that there are 330 risk loci found by genetic association at p≤5x10-8 with systemic lupus erythematosus (SLE) in at least one study of the 160 pertinent publications. There are 225 loci found in East Asian (EAS), 106 in European (EU), 11 in African-American (AA), 18 Mixed American (MA), and 1 in Egyptian (EG) ancestries. Unexpectedly, most of these associations are found to date at p≤5x10-8 in a single ancestry. However, the EAS and EU share 40 risk loci that are independently established. The great majority of the identified loci (250 (75.8%) of 330) do not contain a variant that changes an amino acid sequence. Meanwhile, most overlap with known regulatory elements in the genome (266 (80.6%) of 330), suggesting a major role for gene regulation in the genetic mechanisms of SLE. To evaluate pathways altered by SLE associated variants we generated sets of genes potentially regulated by SLE loci that consist of the nearest genes, published attributions and genes predicted by computational tools. The most useful insights, at present suggest that SLE genetic mechanisms involve: 1) Regulation of both adaptive and innate immune responses including immune cell activation and differentiation; 2) Regulation of production and response to cytokines, including type I interferon, 3) Apoptosis; 4) Sensing and removing immune complexes and apoptotic particles; and 5) Immune response to infections, including Epstein-Barr Virus, and symbiont microorganisms. These mechanisms affected by SLE genes involve multiple cell types including B cells/plasma cells, T cells, dendritic cells, monocytes/macrophages, natural killer cells, neutrophils, endothelial cells and others. The genetics of SLE from GWAS data are revealing an incredibly complex profusion of interrelated molecular processes and iterating cells participating in SLE pathogenesis, mostly unified in molecular regulation of inflammatory responses. These genetic associations in lupus and affected molecular pathways give us not only understanding of the disease pathogenesis but also might help in drug discoveries for SLE treatment.